2005
DOI: 10.1016/j.ejcts.2005.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Importance of implant technique on risk of major paravalvular leak (PVL) after St. Jude mechanical heart valve replacement: a report from the Artificial Valve Endocarditis Reduction Trial (AVERT)☆

Abstract: Suture technique without pledgets is an independent significant risk factor for major PVL events. In this study, use of pledgets during valve replacement had a protective effect against subsequent paravalvular leak, supporting the use of buttress reinforcement for valve suture. The use of Silzone cuff, although not statistically significant, showed a strong trend as a risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
3
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 14 publications
1
33
3
2
Order By: Relevance
“…In the present study, early mitral PVL was recorded in only 1.9% of the patients, contrary to findings of previous studies that early PVL was detected in up to 32% of MVR patients [1,3]. This might be owing to the fact that we avoided the continuous suture technique, which has proved to be associated with a high incidence of PVL after MVR [2,7]. In addition to suture technique, previous studies suggested that the presence of heavy annular calcification, small body surface area, and size and type of prosthetic valve were associated with mitral PVL [1,2,[7][8][9][10].…”
Section: Commentcontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, early mitral PVL was recorded in only 1.9% of the patients, contrary to findings of previous studies that early PVL was detected in up to 32% of MVR patients [1,3]. This might be owing to the fact that we avoided the continuous suture technique, which has proved to be associated with a high incidence of PVL after MVR [2,7]. In addition to suture technique, previous studies suggested that the presence of heavy annular calcification, small body surface area, and size and type of prosthetic valve were associated with mitral PVL [1,2,[7][8][9][10].…”
Section: Commentcontrasting
confidence: 99%
“…This might be owing to the fact that we avoided the continuous suture technique, which has proved to be associated with a high incidence of PVL after MVR [2,7]. In addition to suture technique, previous studies suggested that the presence of heavy annular calcification, small body surface area, and size and type of prosthetic valve were associated with mitral PVL [1,2,[7][8][9][10]. In the present study, however, we could not demonstrate that such factors are associated with incidence of mitral PVL.…”
Section: Commentcontrasting
confidence: 78%
“…Pledgeted sutures to the secure the valve prosthesis to the valve annulus during mitral, aortic, and double mechanical valve replacements have been shown to have a protective effect against postoperative paravalvular leak in comparisons with several different suture techniques. 4 To our knowledge, however, the effect of a uniform, nonpledgeted suture technique during AVR has not been previously well established.…”
mentioning
confidence: 99%
“…Ten years after heart valve replacement, up to 50% of the patients require reoperation or die of complications related to the prosthetic heart valves. There is usually no difference between mechanical and biological prostheses, but the frequency and nature of the complications related to the prostheses vary according to type, model, and valve position, as well as to each patient's characteristics 4,[11][12][13][14][15] . By quantifying the comparative odds ratios between patients who presented varying degrees of prosthetic valve leak, the present study contributes to a better knowledge of its clinical outcome and provides information to guide therapies and establish prognoses.…”
Section: Discussionmentioning
confidence: 99%